Communal Crisis and Livelihoods in Akamkpa (A Regression Analysis Study) - Dormcklaims Enamhe; Egbe E. Tangban; Thomas A. Omang; Mary U. Ojong-Ejoh (PT Mattawang Mediatama Solution, 2021)
Communal crisis and rural community are juxtaposed given the background that Nigeria is anchored upon a conglomeration of cultures with the assumption that cultural heritage should be enjoyable under a benign condition. Unfortunately, societal dynamics emerged with different value systems and new orientations, paving the way for a